Sustancias tóxicas en emisiones gaseosas de incineradores hospitalarios - Bárcena, René (2009)
Toxic substances in gaseous emissions from hospital incineratorsThe Nationallnstitute for Neoplastic Diseases incinerator was studied: emissions were sampled and analyzed for particulate matter (PM), stack gases and vapors and the micrometeorology was also registered. Gases were collected with an isokinetic sampler, total suspended solids by passive sampling. Results show high levels of PM10, which contains Pb, Al, Zn and Ca; high levels of benzene and naphthalene in the gas fireplace. Local dispersion of PM was observed,